Discurso de posse de Lula e Bolsonaro: uma análise das escolhas semântico-discursivas expressas pelos presidentes frente à audiência-nação - Queiroz, Pedro Henrique Ruffo Monteiro de (2022)
The aim of this research is to analyze the discursive formation expressed by presidents Lula and Bolsonaro in front of the nation-audience in their inaugural speeches. To do so, the corpus of analysis is composed by the inauguration speech of President Luiz Inácio Lula da Silva (01/01/2007 – second term) and the inauguration speech of President Jair Messias Bolsonaro (01/01/2019 – first term). The analysis material was sent by the Library of the Presidency of the Republic, thus forming official documents. To guide the research, three questions lead the analysis of the corpus: (i) how do the presidents establish the interaction with the nationaudience?, (ii) in what way do the inaugural speeches of presidents Lula and Bolsonaro are closer or farther in relation to religiosity? and (iii) to what extent is it possible to perceive the other voices that also speak in the presidents' speeches? These are the questions that underlie the specific objectives of this dissertation: (1) interpret the behavior of Brazilian elected presidents before the nation-audience; (2) compare the religious discursive formation in the inaugural speeches of elected presidents; (3) identify polyphony in the inaugural speeches of elected presidents. The theoretical framework on which the research is based is the French Discourse Analysis in dialogue with Textual Linguistics. The results reveal that the speeches of Lula and Bolsonaro are similar in the issue of religiosity that is given by faith in God; and they distance themselves when it comes to religious discourse, since Lula does not use the word of God to distance or denigrate a certain group in society as a whole. Studies also show that both Lula and Bolsonaro resort to what has already been said in their inaugural speeches, revisit ideals, reinforce values and dictate norms according to the memory of the nation-audience. It is still notable, through the results, that both polyphony and the religious discursive formation were guiding pillars of the approximation of presidents with the nation-audience